EKSTERNAL RADYOTERAPİ CİHAZLARINA AİT DOZİMETRİK PARAMETRELERİN ÖLÇÜM VE FABRİKA DEĞERLERİNİN KARŞILAŞTIRMASI - DEMİR, Bayram and Koca, Ayşe and GÜNHAN, Basri and KARAÇAM, Songül and ÖBER, Ahmet (Cerrahpaşa Medical Journal, 2019)
Background and Design.- High energy photon beams which are produced by linear accelerators and Co60 treatment machines are used to treat deep seated tumors in radiotherapy. In this study, parameters, the percent depth doses, dose profiles, penumbras, isodose distributions and beam quality are compared to those given in the manufacturers. atlases. Measurements were performed on a Saturne-42 linear accelerator with photon energies of 6, 15 MV, Orion linear accelerator with 4 MV photon energy, and Co60 treatment machine with 1.25 MeV photon energy .Beam quality measurements made in an RW3 solid water phantom using cylindric ionization chamber and PTW electrometer . Percent depth doses, dose profiles, penumbras, and isodose distribution measurements made in a water phantom. Results.- When the results were compared, the maximum difference in percent depth doses between our measurements and the manufactures. atlases was 5.2 % for 6 MV. At the depth of dose maximum the difference in penumbras found to be within 2 mm. After the comparison of isodose distributions, for 6 MV, 1 cm difference was found between the measured and manufacturers. atlases. Conclusion.- Regarding, it was seen the dosimetric parameters that there were differences in percent depth doses, penumbras, and isodose distributions derived from high energy photon beams between measured data and the ones in the manifacturers. atlases, therefore before starting the treatment with these machines, all dosimetric parameters have to be measured.